2021
DOI: 10.3126/batuk.v7i1.35334
|View full text |Cite
|
Sign up to set email alerts
|

The Consequence of Credit Performance and Capital Adequacy: Evidence from Commercial Banks in Nepal

Abstract: Following random effect GLS model, this study aims at examining the consequence of credit performance and capital adequacy of Nepalese commercial banks. For the analysis, the balanced panel data of 19 commercial banks have judgmentally been selected and used. The researcher took credit to deposit ratio (CDR), interest rate spread (IRS), non-performing loan ratio (NPLR) and capital adequacy ratio (CAR)  as the predictors of profitability measured by return on assets (ROA) of the banks. The results indicate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…On the other hand, the capital ratio of both bank types produced a positive and significant association with ROA, consistent with the many previous findings (Cheng et al, 2020;Islam & Rana, 2022;Kurawa & Garba, 2014;Lew & Lau, 2022;Shrestha & Niraula, 2021;Suganya & Kengatharan, 2018). However, this finding contradicts the studies of Ndoka and Islami (2016) and Bagale (2023), who revealed insignificant relations between these variables.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…On the other hand, the capital ratio of both bank types produced a positive and significant association with ROA, consistent with the many previous findings (Cheng et al, 2020;Islam & Rana, 2022;Kurawa & Garba, 2014;Lew & Lau, 2022;Shrestha & Niraula, 2021;Suganya & Kengatharan, 2018). However, this finding contradicts the studies of Ndoka and Islami (2016) and Bagale (2023), who revealed insignificant relations between these variables.…”
Section: Discussionsupporting
confidence: 87%
“…A thorough approach to risk management must include the efficient management of credit risk NRB (2018). Due to their crucial role on profitability, credit performance and capital adequacy are subject to critical analysis and assessment regarding their effect on profitability performance of banks (Shrestha & Niraula, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…(2020) as they had reported positive impact of CDR on profitability banking. Impact of all three credit risk measures found statistically signifincant and consistent with the finding of Shrestha and Niraula (2021). The result indicated that the increase in nonperforming loan ratio and credit to deposit ratio leads to decrease in profitability whereas the increase in capital adequacy ratio surges banks' ROA in a small ratio (= 0.143, p = 0.000) but multiplies EPS (= 2.793, p = 0.000).…”
Section: Discussionsupporting
confidence: 82%
“…Based on dynamic panel data modelling approach, they revealed a positive and statistically significant relationship between profitability and macroeconomic-specific variables. On the other hand, they found statistically not significant relationship of non-performing loans and capital adequacy with the profitability which is consistent with the findings of Shrestha and Niraula (2021). By analyzing balanced panel data of 19 commercial banks in Nepal, Shrestha and Niraula found significant negative impact of credit to deposit ratio (CDR) and non-performing loan ratio (NPLR) on ROA.…”
Section: Credit Risk External Factors and Profit Of Bankssupporting
confidence: 74%